Proteômica quantitativa, livre de marcação, de Carica papaya L. em resposta à doença da meleira do mamoeiro - Soares, Eduardo de Almeida (2016)
Papaya (C. papaya L), a fruit of great economic importance worldwide, which has suffered huge preharvest losses, mainly by papaya sticky disease (PSD), characterized by spontaneous exudation of aqueous and fluid latex, which oxidizes and accumulates as a sticky substance in the organs of the plant. PSD is caused by a synergic infection by PMeV and PMeV2 viruses, whose symptoms arise only after the juvenile-adult transition (flowering) of the plants. To understand the plant-virus interaction mechanisms and the phenological dependence of the symptoms onset, the C. papaya proteome was accessed by LC-MS/MS-based label-free quantitative proteomic approach for infected and uninfected (control) plants in four different ages (3, 4, 7 and 9 months post germination). This study permitted the identification of 1,623 and quantification of 1,609 proteins, whose the abundances comparison showed an increased levels of photosynthesis related proteins and decreased levels of proteins related to caspase-like activity, 26S-proteasome and cell wall remodeling during asymptomatic stage (prior to the flowering). The onset of the symptoms after flowering (7 months after germination) was accompanied by a reduction in the accumulation of proteins related to photosynthesis and increase in accumulation of proteins related to the metabolism of carbohydrates, lipids, amino acids, proteins, nucleotides and nucleic acids. In addition, was observed the accumulation of proteins involved in response to stress, signaling, transport and cell wall. The sum of these results supports the hypothesis of an incomplete tolerance mechanism in the asymptomatic phase (prior to flowering), with a chloroplast ROS signaling followed by ineffectiveness in containing systemic infection by activity depletion of caspase-like, proteasome, and cell wall remodeling. This incomplete tolerance mechanism at pre flowering acquire new elements with the juvenile-adult transition, which the installed systemic infection, delivers the late and ineffective symptoms of necrotic and chlorotic response. Inhibition in cell wall remodeling processes prior to flowering weakens the latex vessels, which bursts during the PSD osmotic imbalance, leading the sticky aspect of the diseased papaya plants.